Multi-objective optimization of crash box filled with three-dimensional cellular structure under multi-angle impact loading. (August 2021) - Ma, Fangwu; Liang, Hongyu; Pu, Yongfeng; Wang, Qiang; Zhao, Ying
Oblique impact loading conditions are common in automobile collision accidents, which strongly influence the energy absorption performance of thin-walled structures. In this paper, a novel three-dimensional (3-D) hexagonal structure-filled crash box with better comprehensive crashworthiness under multiple working conditions is proposed. First, the finite element models of four 3-D typical cellular structures (hexagon structure, re-entrant hexagon structure, star-shape structure, double arrow structure) are established. The dynamic responses of four structures under different impact angles (from 0° to 30°) and impact velocities (from 5 to 15 m/s) are discussed. The results reveal that the 3-D hexagonal structure has great advantages in terms of the energy absorption at varying inclination angles. Second, the 3-D hexagonal structure is filled in the crash box in the form of gradient distribution. The multi-island genetic algorithm (MIGA) based on the response surface model (RSM) is utilized to explore the optimal design of crash box. Compared with the traditional crash box, the optimal 3-D hexagonal structure-filled crash box increases 18.9% in specific energy absorption and decreases 21.7% in maximum peak force, which demonstrates great potential for applications in impact engineering.